2006
DOI: 10.1121/1.2225382
|View full text |Cite
|
Sign up to set email alerts
|

Temporal characteristics of nasalization in children and adult speakers of American English and Korean during production of three vowel contexts

Abstract: The purpose of this study was to identify and compare the temporal characteristics of nasalization in relation to (1) languages, (2) vowel contexts, and (3) age groups. Two distinct acoustic energies from the mouth and nose were recorded during speech production (/pamap, pimip, pumup/) using two microphones to obtain the absolute and proportional measurements on the acoustic temporal characteristics of nasalization. Twenty-eight normal adults (14 American English and 14 Korean speakers) and 28 normal children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…The work mentioned in [17] and [18] has been a great inspiration for this study. The rest of this paper is organized as follows: Section II presents a brief description of the experiments carried out in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…The work mentioned in [17] and [18] has been a great inspiration for this study. The rest of this paper is organized as follows: Section II presents a brief description of the experiments carried out in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that children exhibit a greater degree of anticipatory coarticulation than adults (Repp, 1986;Nittrouer & Whalen, 1989;Ha & Kuehn, 2006), while other studies indicate that children have less coarticulation than adult speakers (Thompson & Hixon, 1979;Hodge, 1989). A third set studies reported that adults and children exhibit approximately the same amount of coarticulation, yet children exhibited increased variability in their coarticulation (Turnbaugh, Hoffman, & Daniloff, 1985;Sereno, Baum, Marean, & Lieberman, 1987;Katz, Kripke, & Tallal, 1991;Goodell & Studdert-Kennedy, 1993;Katz & Bharadwja, 2001).…”
Section: Developmental Patterns Of Coarticulationmentioning
confidence: 99%
“…On the other hand, in a similar recent study, Ha and Kuehn (2006) compared the temporal characteristics of nasalization between 28 children between four to seven years and 28 adults. The authors obtained measurements of the absolute and proportional durations of the acoustic energy signal associated with VPC in target utterances /pamap/, /pimip/, and /pumup/.…”
Section: Developmental Patterns Of Coarticulationmentioning
confidence: 99%
See 2 more Smart Citations